TURKISH SIGN LANGUAGE EXPRESSIONS RECOGNITION USING DEEP LEARNING AND LANDMARK DATA - Torun, Cumhur; Karacı, Abdulkadir (Mugla Sitki Kocman University, 2024)
Sign language is a vital communication tool for hearing-impaired individuals to express their thoughts and emotions. Turkish Sign Language (TSL) is based on hand gestures, facial expressions, and body movements. In this study, deep learning models were developed to recognize 41 commonly used TSL expressions. An original dataset was created using the Media Pipe Holistic framework to capture the 3D landmarks of hand, face, and body movements. The study trained and evaluated GRU, LSTM, and Bi-LSTM models, as well as hybrid architectures such as CNN+GRU, GRU+LSTM, and GRU+Bi-LSTM. In the training of the models, a hold-out validation method was used. 80% of the dataset was allocated for training and 20% for testing. Additionally, 20% of the training data was used for validation. Among Deep Learning models, the CNN+GRU hybrid model achieved the highest accuracy rate of 96.72%, outperforming similar studies in the literature. Our results demonstrate that deep learning techniques can effectively classify TSL expressions, with the CNN+GRU combination showing particularly high performance. Future work will focus on expanding the dataset and developing real-time recognition systems that incorporate both skeleton images and landmarks.
Keywords: Turkish sign language, Sign language recognition, Media pipe, Deep learning, Recurrent neural network